A Simple Taste Test for Clinical Assessment of Taste and Oral Somatosensory Function—The “Seven-iTT” - Mariano Mastinu; Michał Pieniak; Anne Wolf; Tomer Green; Antje Hähner; Masha Y. Niv; Thomas Hummel (Life, 2022)
Taste dysfunctions may occur, for example, after viral infection, surgery, medications, or with age. In clinical practice, it is important to assess patients’ taste function with rapidity and reliability. This study aimed to develop a test that assesses human gustatory sensitivity together with somatosensory functions of astringency and spiciness. A total of 154 healthy subjects and 51 patients with chemosensory dysfunction rated their gustatory sensitivity. They underwent a whole-mouth identification test of 12 filter-paper strips impregnated with low and high concentrations of sweet, sour, salty, bitter (sucrose, citric acid, NaCl, quinine), astringency (tannin), and spiciness (capsaicin). The percentage of correct identifications for high-concentrated sweet and sour, and for low-concentrated salty, bitter and spicy was lower in patients as compared with healthy participants. Interestingly, a lower identification in patients for both astringent concentrations was found. Based on the results, we proposed the Seven-iTT to assess chemo/somatosensory function, with a cut-off of 6 out of 7. The test score discriminated patients from healthy controls and showed gender differences among healthy controls. This quantitative test seems to be suitable for routine clinical assessment of gustatory and trigeminal function. It also provides new evidence on the mutual interaction between the two sensory systems.